Impact of iodinated contrast media on X-ray-induced DNA damage: a comprehensive review - Chiara Iacconi; Maria Xiarcou; Valeria Piagneri; Enrica Ciofini (Exploration of Cardiology)
Drawing insights from a spectrum of in vitro, in vivo experimental, and clinical studies, this review illuminates the underlying mechanism by which iodinated contrast media (ICM) exerts an indirect genotoxic effect. The mechanism involves the photoelectric effect induced by iodine molecules, thereby augmenting radiation attenuation and subsequently elevating the locally absorbed radiation dose. The ensuing generation of secondary electrons from each photoelectric absorption interaction triggers molecular reactions, culminating in discernible DNA damage, notably in the form of DNA double-strand breaks. A convergence of evidence from in vitro, experimental, and clinical investigations underscores a consistent pattern: the addition of iodine contrast linearly heightens the absorbed radiation dose and associated DNA damage. This quantification was evident through alterations in attenuation and the manifestation of double-strand breaks in circulating lymphocytes, serving as an intermediate endpoint and a potential long-term indicator of cancer. The observed surplus of DNA damage in contrast-enhanced images compared to non-contrast images ranged notably from +30% to +200%. This broad range accentuates a substantial amplification effect on radiation-induced damage, particularly noteworthy at clinically relevant iodine doses. Crucially, this effect remains unaffected by brands or manufacturers and exhibits a robust, exclusive correlation with the concentration of iodine in the bloodstream. The significant augmentation of absorbed dose and genotoxic impact of X-rays due to the use of contrast agents warrants critical attention within the medical community. This often-unacknowledged genotoxic influence may play a pivotal role in elevating cancer risks among patients undergoing radiation-based procedures, necessitating a reconsideration of risk assessment protocols and clinical practices.